Optimization of Oxygen Dynamics, UV-A Delivery, and Drug Formulation for Accelerated Epi-On Corneal Crosslinking. (2nd April 2020) - Hill, Jason; Liu, Cailing; Deardorff, Phillip; Tavakol, Behrouz; Eddington, William; Thompson, Vance; Gore, Dan; Raizman, Michael; Adler, Desmond C.
ABSTRACT: Purpose : Corneal collagen crosslinking (CXL) through an intact epithelium (epi-on) at high irradiance could potentially improve patient comfort, visual recovery, and clinical workflow compared to conventional epi-off CXL. However, intact epithelium limits stromal delivery of the oxygen, photosensitizer, and ultraviolet-A (UV-A) radiation needed to drive CXL. This ex vivo study evaluated three different epi-on CXL protocols compared to positive and negative controls, specifically focusing on the impact of supplemental oxygen. Endpoints included stromal oxygen levels, stiffness of crosslinked tissue, and acute flattening of whole eyes. Materials & Methods : Ex vivo porcine eyes were held in a custom environmental chamber. Intrastromal oxygen levels were continuously measured before, during, and after UV illumination by a fiberoptic probe inserted into a laser-cut flap. Accelerated, high irradiance, epi-on CXL protocols using riboflavin formulated with benzalkonium chloride (BAC) were studied, with and without supplemental oxygen. These were compared to an alternate, low irradiance, epi-on protocol using riboflavin formulated with sodium iodide. Both negative (no CXL) and positive (epi-off modified Dresden protocol) controls were performed. Post-CXL elastic modulus was measured using extensiometry and anterior tangential curvature was measured using a Scheimpflug tomographer. Results : Protocols including supplemental oxygen resulted in an approximately 5-fold increase in stromal oxygen levels prior to CXL. During epi-on, high-irradiance UV-A delivery under hyperoxic conditions, an aerobic state was maintained. Conversely, under normoxic conditions, stromal oxygen rapidly depleted to 0-5% for all other protocols. The combination of supplemental oxygen, BAC formulation, and high-irradiance UV-A resulted in the largest biomechanical changes and most pronounced flattening effects of the three epi-on protocols. Conclusions : Ex vivo analysis of stromal oxygen levels, corneal stiffness, and acute anterior curvature change indicates that simultaneous optimization of the oxygen environment, riboflavin formulation, and UV-A protocol can significantly increase the effects of corneal collagen crosslinking.